Measuring cognitive empathy using story stem narratives - Kwan, Debbie; Barker, Beth; O'Farrelly, Christine; Ramchandani, Paul (Frontiers in Developmental Psychology, 2026)
The measurement of empathy is a challenge, particularly in young children. This study aims to develop a novel measure of cognitive empathy using story stem narratives. Children between 6 and 9 years of age (N = 200) completed two story stem tasks—Hurt Knee and Three's a Crowd—which were used to develop this new measure. Most children were from a white (63.5%) or mixed heritage background (20%), with near equal numbers of male (51.5%) and female (48.5%) child participants. To validate this measure, we tested for psychometric properties including reliability, internal consistency, and concurrent validity. As expected, girls scored higher for cognitive empathy than boys (mean difference = 1.15, 95% CI [0.46, 1.84]). Associations were seen between cognitive empathy and parent-reported prosocial behavior (r = 0.16, p = 0.02), and callous-unemotional traits (r = −0.15, p = 0.02). Using children's representations of their world through story stem narratives could allow for new insights in the study of empathy in young children.